Synergistic effects of antibiotics and fucoidan on dual-species Staphylococcus aureus and Acinetobacter baumannii biofilm in diabetic rat wound models - Mohsen Nazari; Mohammad Taheri; Fatemeh Nouri; Maryam Bahmanzadeh; Mohammad Yousef Alikhani (PLoS ONE, 2026)
Background Chronic diabetic wounds are often complicated by biofilm-forming, antibiotic-resistant pathogens such as Staphylococcus aureus and Acinetobacter baumannii , which delay healing. This study evaluated the synergistic effects of gentamicin and imipenem in combination with fucoidan, a sulfated polysaccharide from brown seaweed, against dual-species biofilms in a diabetic rat wound model. Methods Methicillin-resistant S. aureus (MRSA) strain 6 and A. baumannii strain 1, isolated from diabetic foot ulcers, were used to establish dual-species biofilms in vitro and in vivo. Excisional wounds were created in male Wistar rats with streptozocin-induced type II diabetes and infected with the biofilms. Rats received daily treatments of gentamicin, imipenem, their combination, or the triple combination with fucoidan. Outcomes assessed included bacterial load (CFU/g), biofilm formation, expression of biofilm-related genes ( icaA and bap by real-time PCR), wound size, and histological healing parameters. Results The triple therapy demonstrated the strongest antibacterial effect, reducing bacterial load by more than 4 log₁₀ CFU/g compared to controls (p < 0.005). Real-time PCR revealed significant downregulation of icaA in S. aureus (threefold decrease) and bap in A. baumannii (fourfold decrease) relative to antibiotic-only groups (p < 0.005). Histology showed accelerated wound contraction and complete re-epithelialization by day 14 with the triple combination, whereas monotherapy or dual antibiotics led to delayed healing and persistent inflammation. Conclusions Fucoidan enhances the efficacy of gentamicin and imipenem against biofilm-associated infections and promotes diabetic wound healing. This combinatorial approach offers a promising strategy for managing chronic, biofilm-infected wounds and combating antibiotic resistance.